THU0514 Evidences of A Nontolerogenic-Proinflammatory Surface and Cytokine Phenotype in Monocytes from Patients with Psoriatric Arthritis. (10th June 2014) - Chimenti, M.S.; Bergamini, A.; Baffari, E.; Musto, A.; Guarino, M.D.; Greco, E.; Perricone, R.
Abstract : Background: The immunoglobulin-like transcript-4 (ILT4) is an inhibitory receptor that modulates the activity of innate immune agents. Furthermore, acquisition of an nontolerogenic-proinflammatory phenotype by monocytes may contribute to enhance inflammation and T-cell activation in chronic inflammatory diseases. [1] Objectives: to determine the expression of ILT4 and analysed the relationship with the expression of costimulatory proteins as well as tumor necrosis factor-α (TNFα) production in monocytes from patients with psoriatic arthritis (PsA) starting anti-TNF treatment. Methods: Peripheral blood monocytes from twenty patients with moderate to severe PsA and 15 healthy control subjects were cultured in vitro in the presence of granulocyte macrophage-colony stimulating factor (GM-CSF) and analyzed for the surface expression of innate immune receptor immunoglobulin-like transcript 4 (ILT4), CD40, CD80 and CD86, and CD40L-induced and spontaneous lipopolisaccharide (LPS)-induced TNFα production were evaluated by flow cytometry. Results: The expression of ILT4 was significantly lower in monocytes from patients with PsA compared with cells from controls (percentage of positive cells: 40.4±14.5 vs. 68.6±18.9, P <0.001). Pearson correlation analysis showed that the expression of ILT4 on monocytes from patients with moderate to severe PsA was indirectly correlated with the severity of PsA, measured by DAS44-ESR score (r=-0.654, confidence interval= -0.868 to -0.234, P =0.006). Greater expression of CD40, CD80 and CD86 and enhanced production of TNF-a in response to CD40L stimulation were detected in ILT4 – monocytes from patients with PsA compared with cells from controls. Finally, twelve weeks-treatment with adalimumab resulted in a significant increase of ILT4 expression, a decrease of costimulatory molecules expression and cytokine production in PsA patients, compared to pre-therapy levels. Conclusions: Monocytes of patients with moderate to severe PsA acquire a nontolerogenic-proinflammatory phenotype reverted by anti-TNF treatment. Since monocytes migrate from the peripheral blood into inflamed joints, and GM-CSF acts as a proinflammatory cytokine in different forms of inflammatory arthritis, it is possible to speculate that these phenotypic changes may enhance the antigen presenting ability and the proinflammatory activity of monocytes of PsA patients and then contributes to the autoimmune processes in articular inflammation. This knowledge provides new evidences on the immunomodulatory properties of ILT4 supporting the possibility that changes in the immunophenotype of monocytes play a role in the pathogenesis of PSA. Thus, modulation of the expression of ILT4 may represent an enticing new therapeutic target. References: Dietrich J, Cella M, Colonna M. Ig-like transcript 2 (ILT2)/leukocyte Ig-like receptor 1 (LIR1) inhibits TCR signaling and actin cytoskeleton reorganization. J. Immunol. 2001;166:2514-2521 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1993